2017
DOI: 10.1590/1809-4430-eng.agric.v37n6p1183-1189/2017
|View full text |Cite
|
Sign up to set email alerts
|

Spraying Quality of Crop Protection Products Using Two Droplet Spectra in Three Periods of the Day

Abstract: Spraying of crop protection products can be affected by weather conditions and spray nozzles, altering deposition patterns and coverage of the target surface. The objective of this research was to analyze the quality of sprayings performed in three periods of the day (9:00 am, 2:00 pm, and 6:00 pm), using two different droplet sizes (fine and coarse) in soybeans. Coverage and deposition were evaluated in the upper, middle, and lower portion of soybean canopy. Spraying the products at 2:00 pm increased leaf cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The middle third differentiated from the lower third in DEN, NOD, and COV, while for MVD, the middle and lower thirds did not differ statistically ( Table 2). The upper third of plants have the highest values for spraying rates since this location is the most exposed and unimpeded for spraying (Graziano et al, 2017). Considering the interaction spacing × angle, the angle of 30° presented the highest droplet density when compared to the angles of 45° and 90° in the interrow spacings of 0.22 and 0.45 m. The lower third presented the lowest droplet density in relation to the upper and middle thirds for all angles of displacement.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The middle third differentiated from the lower third in DEN, NOD, and COV, while for MVD, the middle and lower thirds did not differ statistically ( Table 2). The upper third of plants have the highest values for spraying rates since this location is the most exposed and unimpeded for spraying (Graziano et al, 2017). Considering the interaction spacing × angle, the angle of 30° presented the highest droplet density when compared to the angles of 45° and 90° in the interrow spacings of 0.22 and 0.45 m. The lower third presented the lowest droplet density in relation to the upper and middle thirds for all angles of displacement.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, a factor that is not taken into account at the time of application is the sprayer displacement in relation to the arrangement of sowing rows Engenharia Agrícola, Jaboticabal, v.38, n.6, p.927-933, nov./dec. 2018 since the application can occur in the direction, transversal or at an angle to the sowing row (Graziano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the effect of the air supply through a series of works, Oliveira et al (2016) indicated that this mechanism of support to the spray bar had no effect on the performance of agrochemicals and the control levels of phytopathogenic fungi. The contrasting and variable effects on the Vortex ® system may be associated with the different canopy opening levels, which can be influenced by the plant arrangement (Holtz et al, 2014), depending on the characteristic of the cultivar Tormen et al, 2012), as well as by the time of the day of spraying, due to the variation of the horizontal angle of soybean leaves throughout the day (Graziano et al, 2017;Moura et al, 2017). Moreover, the spray tip angle, droplet size and speed, adjuvants and mixture volume are factors that also influence droplets' penetration along the canopy of the plant (Cunha et al, 2014, Madureira et al, 2015Prado et al, 2015;Cunha et al, 2016;Weber et al, 2017, França et al, 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of the application of phytosanitary products and its result in the control of the target are directly related to the choice of nozzles and droplets sizes, the adjustment of application rate, the droplets coverage on the target, favorable environmental conditions for spray deposition, and the ideal application time (GRAZIANO, C. E. et al, 2017). Fine droplets are commonly used potato crops in the application of phytosanitary products (BUENO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the plant mass, the more difficult the droplets penetration and deposition on the lower third of the leaves (BAIO et al, 2018) Thus, fine droplets spray are still used in potato crop to overcome this problem (BUENO et al, 2013). However, fine droplets are more prone to drift, and they evaporate faster, which hinders the control of the target (JIA and ZHU, 2015;GRAZIANO, C. E. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%